What benefits does transparent lobbying bring - Pavla Bednářová (DANUBE: Law, Economics and Social Issues Review, 2018)
Most quantitative studies deal with the costs of transparency lobbying and give little or no attention to quantifying the benefits. The aim of the article is to determine options for increasing lobbying transparency and their evaluation and comparison from the viewpoint of direct and indirect benefits. Regulatory Impact Analysis (RIA) isused. Five basic options are identified. Option I is the possibility of increasing the transparency of lobbying by measures introduced on lobbyists. Option II represents an increase of transparency in terms of lobbying targets. Option III is defined as an increase in lobbying transparency by means of sunshine principles and the increase of lobbying transparency by monitoring and sanctions is included in Option IV. All five options are evaluated from the perspective of realized direct and indirect benefits. The selection of the most suitable option will be carried out in relation with the presupposed incurred regulatory costs of lobbying transparency increase.
Keywords: 330; Transparency; Lobbying; Regulatory Impact Analysis; Cost Benefit Analysis; Regulatory Benefits